PETRI NET MODEL IN THE PROCESS OF SUBMISSION FOR CUSTOMER CREDIT OF BPR LAMBANG GANDA SERANG - Octavia, Megawati; Fitriani, Fitriani; Faisol, Ahmad (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2021)
The credit application process is one of a service that involves queues. This study aims to determine the design of the credit process application service system at the Lambang Ganda Serang Credit Bank using the Petri Net model. This study has 12 places, eight transitions, six operators, and 22 arcs of Petri Net model from credit application service system using Woped 3.2.0 version software